2010
DOI: 10.2527/jas.2009-1940
|View full text |Cite
|
Sign up to set email alerts
|

Influence of benzoic acid and phytase in low-phosphorus diets on bone characteristics in growing-finishing pigs1

Abstract: ABSTRACT:In 2 simultaneous experiments (Exp. 1 and Exp. 2), the effects of benzoic acid (BA) and phytase (Phy) in low-P diets on bone metabolism, bone composition, and bone stability in growing and growing-finishing pigs were examined. Exp. 1 was conducted with 16 crossbred gilts in the weight range of 25 to 66 kg BW, whereas in Exp. 2, 32 crossbred gilts (25 to 108 kg BW) were used. All pigs were individually housed in pens and restrictively fed one of 4 diets throughout the experiment. Total P content of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 30 publications
3
19
0
2
Order By: Relevance
“…Generally, the observed low bone net mineralisation in pigs fed the LP diet is in agreement with other studies confirming that deficient P supply leads to reduced mineral content of bones …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Generally, the observed low bone net mineralisation in pigs fed the LP diet is in agreement with other studies confirming that deficient P supply leads to reduced mineral content of bones …”
Section: Discussionsupporting
confidence: 92%
“…Similar to previous reports, the present results showed that the LP supply was not sufficient to achieve the same overall BMD level in the diaphysis of all four studied bones as the MP and HP supplies. This is supported by previous results showing that decreased P supply to pigs reduced body P retention .…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The effects of BA on bone traits of growing-finishing pigs reported by Bühler et al (2010) are equivocal: Benzoic acid tended to reduce ash concentration in the metatarsal bones, but did not affect the breaking strength of the tibia, despite a significantly reduced tibial bone mineral density. In conclusion, the majority of published data do not show significant negative effects of BA on bone breaking strength and bone ash concentration, suggesting that the risk of reduced bone mineralization caused by this feed additive is low.…”
Section: Discussionmentioning
confidence: 93%